2021
DOI: 10.1111/jipb.13157
|View full text |Cite
|
Sign up to set email alerts
|

Balancing selection and wild gene pool contribute to resistance in global rice germplasm against planthopper

Abstract: Interactions and co-evolution between plants and herbivorous insects are critically important in agriculture. Brown planthopper (BPH) is the most severe insect of rice, and the biotypes adapt to feed on different rice genotypes. Here, we present genomics analyses on 1,520 global rice germplasms for resistance to three BPH biotypes. Genome-wide association studies identified 3,502 single nucleotide polymorphisms (SNPs) and 59 loci associated with BPH resistance in rice. We cloned a previously unidentified gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…Alternatively, the breeding and cultivation of resistant rice cultivars is more effective and environmentally friendly. In the past few decades, over 40 BPH resistance genes have been identified in rice, 11 of which have been successfully cloned [ 6 , 7 , 8 , 9 ]. Nonetheless, how these genes confer effective BPH resistance remain elusive, as reports on the mechanism underlying BPH resistance have been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the breeding and cultivation of resistant rice cultivars is more effective and environmentally friendly. In the past few decades, over 40 BPH resistance genes have been identified in rice, 11 of which have been successfully cloned [ 6 , 7 , 8 , 9 ]. Nonetheless, how these genes confer effective BPH resistance remain elusive, as reports on the mechanism underlying BPH resistance have been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Rice varieties that are resistant to BPH can inhibit the pest’s feeding, growth, and fecundity ( Zheng et al, 2021 ). In recent decades, many BPH resistance genes and QTLs have been detected in cultivated rice and wild species ( Guo et al, 2018 ; Shi et al, 2021 ; Zhou et al, 2021 ). However, new BPH biotypes may evolve that are virulent to resistant rice varieties ( Claridge and Den Hollander, 1980 ; Saxena et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous genome‐wide association analyses identified 3502 SNPs and 59 loci associated with BPH resistance in rice (Zhou et al ., 2021), which may have important implications for the control of BPH. Here, we observed that SNP8 and SNP9 in the OsCslF6 promoter produced an AT‐rich domain in the AA allele, but not in the AT or TT alleles (Figure 4a,b).…”
Section: Discussionmentioning
confidence: 99%